2021
DOI: 10.1093/sleepadvances/zpab016
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype as self-regulation: morning preference is associated with better working memory strategy independent of sleep

Abstract: Study objectives We set out to examine how chronotype (diurnal preference) is connected to ability to function in natural conditions where individuals cannot choose their sleep schedule. We conducted a cross-sectional study in military conscript service to test the hypothesis that sleep deprivation mediates the adverse effects of chronotype on cognitive functioning. We also examined the effects of time of day. Methods 140 par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 83 publications
2
4
0
Order By: Relevance
“…Overall, the present results are mostly in line with the findings challenging the synchrony effect on cognition (e.g., Ceglarek et al, 2021;Heimola et al, 2021Heimola et al, , 2021Knight & Mather, 2013;Lewandowska et al, 2018;Li et al, 1998;Matchock & Mordkoff, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Overall, the present results are mostly in line with the findings challenging the synchrony effect on cognition (e.g., Ceglarek et al, 2021;Heimola et al, 2021Heimola et al, , 2021Knight & Mather, 2013;Lewandowska et al, 2018;Li et al, 1998;Matchock & Mordkoff, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…From a positive perspective, our results can be interpreted that the synchrony effect does exist and that it would emerge in about 25% of cognitive tasks (i.e., 2/8 of our tasks). From this perspective and based on the assumption that a large portion of null-findings are not published (e.g., Kühberger et al, 2014), our findings would be broadly consistent with previous research showing mixed evidence with regards to the synchrony effect on short-term memory and working memory (e.g., Rowe et al, 2009;Schmidt et al, 2015;West et al, 2002;but Ceglarek et al, 2021;Heimola et al, 2021;Lewandowska et al, 2018). This interpretation of the findings would be valid if the circumstances under which a synchrony effect occurs and under which it does not occur were clear.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As a result of the study, it was found that morningness chronotypes had a better cognitive capacity than eveningness chronotypes, with reduced P300 delay observed for both frequent and rare stimuli (Venkat et al 2020). In the study of Heimola et al it was found that working memory was associated with chronotypes, and morningness chronotypes performed better (Heimola et al 2021). A study conducted with adolescents in Japan found that 51.1% of the participants experienced ≥1 hour of social jetlag.…”
Section: How Does Chronotype and Social Jetlag Affect Neurocognitive ...mentioning
confidence: 96%